Skin Adnexal Tumors: A study of 26 cases - Viswanathan, Vidya; Dharwadkar, Arpana; Vimal, Shruti; Bhandari, Parul; Malhotra, Aditi; Paul, Barnali (Annals of Pathology and Laboratory Medicine, 2020)
Background: Skin adnexal tumours are a category of rare tumours. They usually present as painless nodules and papules. The diagnosis of these tumours poses a challenge, because there is usually a discrepancy in clinical and histopathological diagnosis. Aims: To study the skin biopsies received in our department and compare their clinical and histopathological diagnosis. Material and methods: Prospective study of skin biopsies received in our department over a period of 1 year. The biopsies were processed and stained with haematoxylin and eosin and studied under the light microscope. Results: Out of the 26 cases studied, 25 were found to be benign tumours with a single case of keratoacanthoma. The most common tumour encountered was pilomatricoma and the least common was syringoma. Only four cases showed clinical correlation with histopathological diagnosis. Conclusion: It can be therefore concluded that skin adnexal tumours are rare tumours which need histopathological examination for their accurate diagnosis.